Gembyangan Waranggana: The Process of Abjection toward Warangganas and Langen Tayub Tradition. - Mujahidah, Affaf (UIN Sunan Kudus, 2020)
The concept of representation of Dewi Sri manifested in the Langen Tayub performance. However, as the massive development in Javanese society, the image of warangganas has gradually derogated. Even waranggana has been synonymous with prostitute, being a waranggana is not similar to be a sexual worker. There are many requirements of being a waranggana. Not only must able to sing obligatory gendhings, a waranggana is required to be a good dancer. Therefore, a waranggana training system was established in Ngrajek, Sambirejo, Tanjunganom, Nganjuk regency, East Java. The procession of graduation from this training has been an annual tourism agenda of Nganjuk regency, called gembyangan waranggana. The existence of training system for waranggana has been an antithesis of pejorative image of warangganas. Therefore, this paper aims to analyze on the existence of waranggana training system in Nganjuk. Refers to Kristeva idea of abjection of women role, this paper will focus on how the negative perception of warangganas has been formulated. Moreover, the discussion of government policies for managing this training system will be another highlight. The first chapter will be an introduction which represented by the history of gembyangan waranggana. The second chapter will explain the process being a good waranggana and skills have to be mastered. Then will continue by the social condition of waranggana and the society’s perception toward them. All chapters will be wrapped up by the last chapter, discussion.